The RTI act and training - Brief comments on capacity building at the state level - Hooja, Rakesh (2009)
The capacity building initiatives in the wake of enactment of RTI Act require a strong emphasis on conceptual clarity and sensitisation towards the utility and importance of the Act. In fact, everybody in the state governments needs to be trained and oriented about the new information regime. there is a need to develop a culture throughout the government that is oriented towards transparency in the systems. Besides the requirements of the new act, the officials at various levels also need to be trained in effective and improved record management by deploying latest available techniques and technology. Courses on evolving office procedures conducive to the RTI? Should also make part of the capacity building curriculum. - Reproduced.
Keywords: Training; Right to information